AN APPLICATION OF STANDARD COSTS IN THE FIELD OF DISTRIBUTION (AN ACTUAL CASE). - Harris, Gould L. (The Accounting Review, 1931)
Standard costs, so-called, had their genesis in the field of production but are being applied more and more in the field of distribution. This paper deals with only one application to the latter field. The technique of the application will be described first then reasons for the method and finally advantages of the plan. The plan might be called "The Key Man Incentive Plan." For point values assigned for weighting sales the first step in the procedure is to establish a scale of points per $1,000 of sales of product for certain spreads of margins of profit over manufacturing cost. A statement is then prepared listing various products or groups of products, their profit margins over manufacturing cost their sales points based upon these margins, any policy adjustments made to the latter in order to determine the final sales points assigned to each product or groups of products. The purpose of establishing these sales points based upon profit margins is to enable one to weight the sales volume so as to indicate the relative desirability of securing business for various products from the standpoint of both normal profit and proper balancing of factory operations.